Changes in the mechanical properties of human quadriceps muscle after eccentric exercise - Philippou, A.a , Maridaki, M.b , Bogdanis, G.b , Halapas, A.a , Koutsilieris, M.a (In Vivo, 2009)
Muscular adaptation which occurs following eccentric exercise-induced muscle damage has been associated with changes in the mechanical properties of muscle manifested as a shift in the length-tension relationship towards longer muscle lengths. However, it is not clear whether this shift is a long term adaptation to eccentric exercise. The purpose of this study was to investigate functional adaptations to skeletal muscle damage in humans, tracking such responses several days into muscle recovery. Ten healthy young men performed an eccentric exercise protocol involving the quadriceps muscle and functional measurements were performed before and on days 1, 2, 5, 8, 12 and 16 post-exercise. Blood samples were also withdrawn before and at 6 h, and 2 days, 5 days and 16 days post-exercise. The exercise protocol resulted in muscle damage, indicated by changes in clinical markers including increased serum creatine kinase activity and muscle soreness compared to pre-exercise levels (p<0.05-0.001). An acute, but not sustained shift in the quadriceps isokinetic and isometric angle-torque curves towards longer muscle lengths was observed post-exercise (p<0.05). It was speculated that the functional adaptations following eccentric exercise might be affected by the short resting and functional length of the quadriceps muscle, relative to its optimum. More studies are needed to confirm the hypothesis that a sustained shift in the muscle's length-tension relationship, as an adaptation after lengthening contraction-induced damage, is muscle specific.